DEVELOPING INTERACTIVE MULTIMEDIA FOR TEACHING DESCRIPTIVE TEXTS BASED ON PALEMBANG LOCAL CULTURE - Ria Elviana; Rita Inderawati; Soni Mirizon (Indonesian EFL Journal, 2020)
The purpose of this study was to find out the validity, practicality, and potential effect of the developed interactive multimedia for teaching descriptive texts based on Palembang local culture. With Research and Development (RD) study, this research procedure was adapted from ADDIE model consisted of five phases, i.e. analysis, design, development, implementation, and evaluation. In evaluation phase, formative evaluation which consisted of self-evaluation, expert review, one to one evaluation, small group evaluation, and field test. Formative evaluation was conducted to see the validity, practicality, and potential effect of the product. Validity was evaluated in expert review phase for its content, construct, and media. Based on experts review the result showed that the average score of all aspects of the developed product was 3.58 which can be categorized as very highly valid. The practicality was evaluated in one to one evaluation and small group evaluation. The result showed that the product was very highly practical since the average score in both phases were 3.69 and 3.74 respectively. The potential effect was evaluated in the field test. The product also had very high potential effect after being tried out in the field test as 100 % of the students achieved the minimum mastery criterion which was 75. In conclusion, the developed product was potentially effective to be applied for the tenth grade students.Keywords: development research; interactive multimedia; descriptive texts; Palembang local culture